Performance Audit of National Rural Health Mission (NRHM) in Uttarakhand (2008-2013) - CAG of India (CAG of India)
This performance audit of National Rural Health Mission (NRHM) in Uttarakhand for the period 2008-2013 revealed that Household surveys and facility surveys intended for identifying the healthcare needs of the people at bottom level were not conducted in the State. District Health Action Plans for the year 2008-09 to 2012-13 were prepared without aggregating the Block and Village Health Action Plans. Against the availability of Rs 778.28 crore during 2008-09 to 2012-13, Rs 650.10 crore were spent and Rs 12.41 crore were returned to Gol, thereby, leaving Rs 115.77 crore unspent. Despite incurring an expenditure of Rs 64.23 crore, the Department failed to get any input in planning and monitoring of implementation of NRHM from VHSSCs, besides utilization certificates for Rs 330.44 crore were also not obtained from VHSSCs. Under Janani Suraksha Yojana, the Department made delayed payment of Rs 32.98 crore to the beneficiaries. Due to excessive procurement, Drug Kits (A&B) valued at Rs 1.21 crore expired in Drug Warehouse and equipment worth Rs 2.18 crore were lying idle in the test-checked CHCs and PHCs. An undue payment of Rs 7.95 crore was made to a service provider (108-emergency response services) and operational cost of Rs 3.20 crore was also not recovered from it.
For the Period 2008-2013